Navigating English Language Education Challenges in Resource-limited Contexts - Singh, Ramesh Bahadur (KMC Journal, 2024)
Nepal's diverse linguistic landscape challenges the under-resourced education system, particularly in teaching English. Despite the demand for English from parents and communities due to globalization, rural schools still face difficulties in providing English language education, despite student, parent, and community expectations, and government policies. The purpose of this study was to explore the challenges faced by English language teachers in an under-resourced context and their coping strategies in Nepal. A qualitative research approach with the narrative inquiry was used and two public secondary schools from Dadeldhura district of Nepal were chosen for the study area. An in-depth interview was conducted to assess the participants’ information. The findings revealed that implementing student-centered learning, navigating the new English curriculum, overcoming limited teaching resources, and managing overcrowded classrooms emerge as significant challenges for English teachers. The results showed that to overcome the challenges, teachers emphasize vocabulary development, utilize alternative teaching methods and materials, engage interactive teaching methods, and motivate students to learn English. This study emphasizes the challenges in English language education in rural schools of Nepal, including weak language skills, limited resources, and overcrowded classrooms. Alternative methods and personal devices were used to overcome limitations. Vocabulary enhancement and motivation are prioritized.